Cover Picture: Light‐Regulated Stapled Peptides to Inhibit Protein–Protein Interactions Involved in Clathrin‐Mediated Endocytosis (Angew. Chem. Int. Ed. 30/2013). Issue 30 (1st July 2013) - Nevola, Laura; Martín‐Quirós, Andrés; Eckelt, Kay; Camarero, Núria; Tosi, Sébastien; Llobet, Artur; Giralt, Ernest; Gorostiza, Pau
<x xml:space="preserve">Abstract</x> Remote control of membrane traffic is described by E. Giralt, P. Gorostiza, et al. in their Communication on page 7704 ff. Photoswitchable inhibitors of protein–protein interactions have been applied to photoregulate clathrin‐mediated endocytosis in living cells. Traffic light peptides constitute a new tool to control cell signaling in spatiotemporally defined patterns and can be used to dissect the role of clathrin‐mediated endocytosis in receptor internalization and in cell growth, division, and differentiation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>